Perception of COVID-19 Pandemic Among IBD Clinicians and IBD Surgeons in Black Sea Region: A Cross-Sectional Questionnaire Study - Celasin, Haydar; Törüner, Murat; Aghayeva, Sevda; Bayramov, Nuru; Vardanyan, Armen; Nanaeva, Bella; Dardanov, Dragomir; Podpriatov, Sergii; Dorofeyev, Andriy; Geçim, İbrahim Ethem (Turkish Journal of Gastroenterology, 2022)
Background: Since December 2019, the COVID-19 pandemic has created an increasing challenge in managing inflammatory bowel dis- ease patients both medically and surgically. Although several international and national medical/surgical associations published guide- lines in this area, there is still a huge difference between daily practices and these guidelines, especially depending on regional practices and governmental policies. Therefore, we aimed to investigate and define gastroenterologists’ and surgeons’ fear of COVID-19 and how they have managed inflammatory bowel disease patients during this pandemic in the Black Sea region. Methods: A 20-question survey was administered to 70 gastroenterology specialists and 80 general surgeons who are mainly focused on the management of inflammatory bowel disease in 5 countries in the Black Sea region. Results: The majority of respondents (81.3%) mentioned that they have concerns that their inflammatory bowel disease patients were at risk of contracting COVID-19. In addition, the majority of respondents (80.3%) believed that inflammatory bowel disease itself, inde- pendent of medications, might increase the risk of contracting COVID-19. The majority of gastroenterologists told that they did not stop inflammatory bowel disease medications due to the COVID-19 pandemic unless patients had COVID-19 disease. Surgeons overwhelm- ingly reached a consensus on how to test patients for COVID-19 perioperatively and came to a conclusion on which of the patients can- not wait to be operated. Both gastroenterologists and general surgeons, usually have similar perceptions. Conclusion: Despite the increasing number of definitive studies, it seems that there are still regional differences in the perception of COVID-19 and inflammatory bowel disease patient care during the pandemic. Cite this article as: Celasin H, Törüner M, Aghayeva S, et al. Perception of COVID-19 pandemic among IBD clinicians and IBD surgeons in Black Sea region: A cross-sectional questionnaire study. Turk J Gastroenterol. 2022;33(12):1004-1011.